Intermittent antipsychotic medication and mortality in institutionalized older adults: A scoping review. (23rd April 2019) - Randle, Jason M.; Heckman, George; Oremus, Mark; Ho, Joanne
Abstract : Objective/Background: Antipsychotic use appears to increase mortality risk among older adults with dementia. Whether this risk is similar for regular or intermittent use is unknown. This scoping review aims to explore the temporal association between antipsychotic use and mortality risk for older institutionalized adults. Method: We conducted a scoping review using Medline (PubMed), EMBASE, CINAHL, and the Cochrane libraries between October 2018 and January 2019. Results: Twenty‐eight articles met review criteria. We found that different antipsychotic medications present different safety profiles. The risk of mortality was highest with conventional antipsychotic use and within 40 days of antipsychotic initiation. Conclusions: Conventional antipsychotic use increases mortality for older institutionalized adults. The evidence for atypical antipsychotics is less clear. Mortality risk appears highest within 30 to 40 days of initiating antipsychotic treatment. This temporal association suggests increased mortality may actually be the result of some previously unrecognized illness, comorbidity, change in health status, or increased frailty, rather than an idiosyncrasy of the antipsychotic itself.